Reformasi Kekosongan Hukum Dalam Eksekusi Putusan Tindak Pidana Lingkungan Hidup Terhadap Pengelolaan Limbah B3 - Ngamilatun, Ngamilatun; Kusumaningrum, Anggraeni Endah (Jurnal JURISTIC, 2025)
The execution of decisions in environmental crime cases, particularly those related to the management of Hazardous and Toxic Waste (B3), often faces various obstacles due to legal vacuums that hinder the implementation of penalties. Legal reform in this context becomes crucial to ensure that law enforcement against environmental violations can operate effectively and justly. This research employs a normative juridical method with an approach to legislation, case studies, and conceptual analysis. Data is obtained from legal literature reviews as well as the analysis of court decisions related to environmental crimes. This study discusses the reform efforts needed to address legal vacuums, focusing on improving regulations and decision execution mechanisms. Various challenges faced in executing decisions on environmental crimes are also outlined, including limited resources, unclear technical regulations, and lack of coordination among related institutions. With the right reforms, it is expected that there will be an increase in effectiveness in environmental protection through more stringent enforcement against violations of hazardous waste management.